2015
DOI: 10.1016/j.coal.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Seismic monitoring and analysis of excessive gas emissions in heterogeneous coal seams

Abstract: Uncontrolled and excessive gas emissions pose a serious threat to safety in underground coal mining. In a recently completed research project, a suite of monitoring techniques were employed to assess the dynamic response of the coal seam being mined to longwall face advance at Coal Mine Velenje in Slovenia. Together with continuous monitoring of gas emissions, two seismic tomography measurement campaigns and a microseismic monitoring programme were implemented at one longwall top coal caving panel. Over 2,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 34 publications
(39 reference statements)
2
32
0
Order By: Relevance
“…Fig. 2a presents an example of the spatial distribution and the energy level, represented by the size of individual circles, of the microseismic events recorded at Coal Mine Velenje over one production week (Si et al, 2015a). The corresponding histogram of the magnitude of the recorded energy is presented in Fig.…”
Section: Fracture Size Rangementioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 2a presents an example of the spatial distribution and the energy level, represented by the size of individual circles, of the microseismic events recorded at Coal Mine Velenje over one production week (Si et al, 2015a). The corresponding histogram of the magnitude of the recorded energy is presented in Fig.…”
Section: Fracture Size Rangementioning
confidence: 99%
“…In a previous study by the authors (Si et al, 2015a), it was observed that the range of seismic energy released spanned by up to four orders of magnitude (from 10 2 to~10 6 J).…”
Section: Analysis Of Mining-induced Microseismic Events At Coal Mine mentioning
confidence: 99%
See 1 more Smart Citation
“…In underground coal mining systems, coal wall spalling, gas emissions, and unexpected roof falling are serious disasters increasing the economic cost and challenging the security of coal production, especially when the coal seam is soft and weak [1][2][3]. The stability of soft coal seam is difficult to control due to the relatively low mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers suggested using gas pressure, coal bed stresses, and methane concentration parameters based on these characteristic pieces of information to predict CGOB disasters. The main contactless monitoring and early warning methods to predict the CGOB disasters include electromagnetic radiation (EMR) method [15][16][17][18], acoustic emission (AE) method [19,20], and microseismic (MS) method [21]. Compared with AE and EMR, MS inversion technology exhibits advantages in source inversions, monitoring range, and signal connotation aspects over a large size monitoring range [22][23][24].…”
Section: Introductionmentioning
confidence: 99%